2021
DOI: 10.1088/1361-6463/abefbc
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma ammonia synthesis over mesoporous silica SBA-15

Abstract: Herein we demonstrate the synthesis of ammonia via atmospheric dielectric barrier discharge plasma discharge over silica. We evaluated the performance of three structural different silicas: non-porous silica, fumed-silica and mesoporous SBA-15 silica. The mesoporous SBA-15 sample resulted in an ammonia synthesis rate per gram of catalyst at least three times higher than that of the non-porous and fumed silica when employing a hydrogen rich gas feed. The hierarchical ordered pore size in the mesoporous range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 49 publications
3
35
0
Order By: Relevance
“…The importance of ER reactions is expected to be great at the high radical densities typically present in DBD plasmas. ,, To what extent plasma-activated species can penetrate the pores of the catalyst and interact with the active metal sites and how plasma-activated species interact with support materials can be an important descriptor for efficient catalyst design. The mesoporous nature of zeolites and MOFs retains specific interest to enhance diffusion of plasma species and/or alter plasma characteristics that could help further optimization of the technology. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of ER reactions is expected to be great at the high radical densities typically present in DBD plasmas. ,, To what extent plasma-activated species can penetrate the pores of the catalyst and interact with the active metal sites and how plasma-activated species interact with support materials can be an important descriptor for efficient catalyst design. The mesoporous nature of zeolites and MOFs retains specific interest to enhance diffusion of plasma species and/or alter plasma characteristics that could help further optimization of the technology. …”
Section: Resultsmentioning
confidence: 99%
“…19 In addition, microporous phases, like zeolites and metalorganic frameworks (MOFs), can also improve diffusion of the plasmaactivated species toward the active sites. 20,21 For a realistic representation of plasma-catalytic NH 3 synthesis, different plasma conditions must be accounted for. Therefore, in this paper we discuss the surface kinetics, (i) in the microdischarges of a filamentary plasma, (ii) in between the microdischarges of a filamentary plasma, and (iii) in a uniform plasma.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Compared with the conventional HB process, the NTP catalytic route can be operated under milder conditions and powered by intermittent electricity (generated from renewable solar and wind), allowing a small-scale and intermittent operation. 15,17 Recently, the rational screening and designing of proper packing materials and catalysts for NTP catalytic reactor are important to improving the catalytic performance in terms of reactant conversion, product yield, and energy efficiency. 20 Recent efforts have demonstrated that the use of porous materials (e.g., zeolite, 15,17 metal−organic frameworks 21,22 ) is highly appealing to greatly improve the performance of NTP catalytic ammonia synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…15,17 Recently, the rational screening and designing of proper packing materials and catalysts for NTP catalytic reactor are important to improving the catalytic performance in terms of reactant conversion, product yield, and energy efficiency. 20 Recent efforts have demonstrated that the use of porous materials (e.g., zeolite, 15,17 metal−organic frameworks 21,22 ) is highly appealing to greatly improve the performance of NTP catalytic ammonia synthesis. For example, Gorky et al demonstrated the presence of mesoporous SBA-15 in the NTP reactor could promote the formation and possible diffusion of microdischarges.…”
Section: Introductionmentioning
confidence: 99%